2022
DOI: 10.3389/fmed.2022.864972
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Generation of In-House Serological Assays Is Comparable to Commercial Kits Critical for Early Response to Pandemics: A Case With SARS-CoV-2

Abstract: IntroductionAccurate and sensitive measurement of antibodies is critical to assess the prevalence of infection, especially asymptomatic infection, and to analyze the immune response to vaccination during outbreaks and pandemics. A broad variety of commercial and in-house serological assays are available to cater to different laboratory requirements; however direct comparison is necessary to understand utility.Materials and MethodsWe investigate the performance of six serological methods against SARS-CoV-2 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is more diversity, however, of reported outcomes with regards to the strength of this correlation than there is with sensitivity and specificity. Wilkins et al [12] , Jochum et al [23] , Auerswald et al [25] , and Takei et al [31] report relatively high correlation coefficients (Spearman's / Pearson’ r in the range of 0.7 – 0.85), while Einhauser et al [14] have reported moderate correlation (0.53) between the two assays. Rus et al [24] reported a Cohen's Kappa of 0.56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is more diversity, however, of reported outcomes with regards to the strength of this correlation than there is with sensitivity and specificity. Wilkins et al [12] , Jochum et al [23] , Auerswald et al [25] , and Takei et al [31] report relatively high correlation coefficients (Spearman's / Pearson’ r in the range of 0.7 – 0.85), while Einhauser et al [14] have reported moderate correlation (0.53) between the two assays. Rus et al [24] reported a Cohen's Kappa of 0.56.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] have also ascertained clinical sensitivity of the assay after exposure to the SARS-CoV-2 virus or vaccine or both, and specificity through evaluation of pre-pandemic specimens. Sensitivities have been reported at time intervals varying from 14 days to 240 days post-exposure.…”
Section: Resultsmentioning
confidence: 99%
“…There is also strong evidence that in the areas of the globe with low income and high population density, where there is a high probability of eCOVID exposure, the mortality and morbidity from SARS-CoV-2 have been low (discussed in a later section; Tables 4–6 ). Our understanding of the cross-immunity induced by eCOVID infection is limited and the only evidence is that children are significantly less susceptible to SARS-CoV-2 and in low-income, high-density regions of the world where continuous exposure to eCOVIDs is evident, the serious incidence of SARS-CoV-2 associated hospitalization and death are significantly low [ 22–27 ]. Several recent studies have shown that a considerable proportion of individuals without a history of SARS-CoV-2 infection possess antibodies to SARS-CoV-2 and SARS-CoV-2-reactive T cells, indicating that cross-reactive T cell subsets originating from past infections by eCOVID may play a role in the clinical outcome of infection with the phylogenetically related eCOVID [ 3–8 ].…”
Section: Introductionmentioning
confidence: 99%